The impact of coronavirus disease 2019 (COVID-19) on the antimicrobial stewardship pharmacist workforce: A multicenter survey - Megan R. Wimmer; Lucas T. Schulz; Ashlee G. Hamel; Rebecca J. Schwei; Karen Fong; Donna R. Burgess; Meghan Brett; Cory M. Hale; Marisa Holubar; Rupali Jain; Rachel Larry; Emily S. Spivak; et al. (Cambridge University Press, 2022)
Abstract Objective: The coronavirus disease 2019 (COVID-19) pandemic has required healthcare systems and hospitals to rapidly modify standard practice, including antimicrobial stewardship services. Our study examines the impact of COVID-19 on the antimicrobial stewardship pharmacist. Design: A survey was distributed nationally to all healthcare improvement company members. Participants: Pharmacist participants were mostly leaders of antimicrobial stewardship programs distributed evenly across the United States and representing urban, suburban, and rural health-system practice sites. Results: Participants reported relative increases in time spent completing tasks related to medication access and preauthorization (300%; P = .018) and administrative meeting time (34%; P = .067) during the COVID-19 pandemic compared to before the pandemic. Time spent rounding, making interventions, performing pharmacokinetic services, and medication reconciliation decreased. Conclusion: A shift away from clinical activities may negatively affect the utilization of antimicrobials.